2023
DOI: 10.1029/2022gl100747
|View full text |Cite
|
Sign up to set email alerts
|

A Large New Crater Exposes the Limits of Water Ice on Mars

Abstract: The mid-latitudes are critical for understanding the recent climate of Mars. Temperature and atmospheric water vapor control subsurface water ice stability (e.g., Chamberlain & Boynton, 2007;Mellon & Jakosky, 1995;Mellon et al., 2004), with colder temperatures and higher humidity causing shallower ice. Shallow ice is ubiquitous at high latitudes (e.g., Boynton et al., 2002;Smith et al., 2009) and stable at depths of centimeters (e.g., Mellon et al., 2004). At mid-latitudes warmer temperatures increase the dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The breakup of an impactor of the size required to produce the S1222a would have produced a widely‐strewn spread of primary craters, of which there is no evidence in the high‐resolution images. Furthermore, even if the main crater were hidden by steep topography, a large strewn field of craters would similarly be expected (Dundas et al., 2023), yet none is observed.…”
Section: Resultsmentioning
confidence: 98%
“…The breakup of an impactor of the size required to produce the S1222a would have produced a widely‐strewn spread of primary craters, of which there is no evidence in the high‐resolution images. Furthermore, even if the main crater were hidden by steep topography, a large strewn field of craters would similarly be expected (Dundas et al., 2023), yet none is observed.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, ice excavations at impact craters show near-surface ice down to latitudes of 35°N (Byrne et al, 2009;Dundas et al, 2014Dundas et al, , 2021Dundas et al, , 2023. These exposed ice chunks may be more like pure ice than pore-filling due to the low regolith content in the ice (Dundas et al, 2014(Dundas et al, , 2021(Dundas et al, , 2023. In each case, our model, as well as those of Chamberlain and Boynton (2007), Mellon et al (2004), and Schorghofer and Aharonson (2005) do not predict stable ice at these locations with current humidity (Figure 3).…”
Section: Possible Presence Of Unstable Water Icementioning
confidence: 85%
“…Finally, ice excavations at impact craters show near‐surface ice down to latitudes of 35°N (Byrne et al., 2009; Dundas et al., 2014, 2021, 2023). These exposed ice chunks may be more like pure ice than pore‐filling due to the low regolith content in the ice (Dundas et al., 2014, 2021, 2023). In each case, our model, as well as those of Chamberlain and Boynton (2007), Mellon et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were larger broadband (BB)-type events at much greater, teleseismic distances. These events allowed the deeper crustal structure of Mars to be probed (Kim et al 2022) and also uncovered the nearest-equatorial water ice ever found on Mars (Dundas et al 2022).…”
Section: Introductionmentioning
confidence: 92%